2018
DOI: 10.1097/mbc.0000000000000679
|View full text |Cite
|
Sign up to set email alerts
|

Molecular diagnosis of factor XIII deficiency, data from comprehensive coagulation laboratory in Iran

Abstract: : Diagnosis of factor XIII (FXIII) deficiency (FXIIID) as a rare bleeding disorder is a challenge worldwide. Thus, in the present study, we used different methods including two molecular methods for detection of FXIIID. This study was conducted on individuals suspected to FXIIID. All individuals were checked by two routinely used methods of clot solubility test in Iran and two other clot solubility tests as well as FXIII activity and antigen assays. Molecular analysis was performed by PCR-restriction fragment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…[10][11][12][13][14][15] Although the diagnosis of FXIII deficiency in Iran is still performed mostly by means of clot solubility tests, using 1% monochloroacetic acid (MCA) and 5M urea, several newer and improved diagnostic techniques, including FXIII activity assays and molecular analysis are growing in use in recent years. It has been shown that clot-solubility tests cannot detect all patients with severe FXIII deficiency in southeastern Iran, 16,17 which is similar to experience seen elsewhere. 18 Although UCB is the leading clinical symptom leading to a diagnosis of FXIII deficiency, both in Iran and worldwide, ICH is the main cause of death in these patients.…”
Section: A Mini-review Of Prior Art In Relation To Factor XIII Deficisupporting
confidence: 77%
See 1 more Smart Citation
“…[10][11][12][13][14][15] Although the diagnosis of FXIII deficiency in Iran is still performed mostly by means of clot solubility tests, using 1% monochloroacetic acid (MCA) and 5M urea, several newer and improved diagnostic techniques, including FXIII activity assays and molecular analysis are growing in use in recent years. It has been shown that clot-solubility tests cannot detect all patients with severe FXIII deficiency in southeastern Iran, 16,17 which is similar to experience seen elsewhere. 18 Although UCB is the leading clinical symptom leading to a diagnosis of FXIII deficiency, both in Iran and worldwide, ICH is the main cause of death in these patients.…”
Section: A Mini-review Of Prior Art In Relation To Factor XIII Deficisupporting
confidence: 77%
“…We have found that neither the clot solubility test nor the FXIII activity assay detects all patients with severe FXIII deficiency, while a molecular study with a simple polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) can instead detect all patients. 16 Comparatively, the tetra-primer amplification refractory mutation system-PCR (T-ARMS-PCR) as a cost-benefit molecular method has failed to detect all cases with FXIII deficiency. 16 All patients with confirmed FXIII deficiency prophylactically receive Fibrogammin P in a dose of 10 IU/ kg every 4 weeks from the time of diagnosis.…”
Section: A Mini-review Of Prior Art In Relation To Factor XIII Deficimentioning
confidence: 99%
“…ICH is the main cause of morbidity and mortality in congenital FXIII deficiency. Due to the rarity of congenital FXIII deficiency, there is a paucity of data in the literature about the pathogenesis and underlying factors of ICH in this disorder [3][4][5][6]. According to the previous studies, MMP-2 and MMP-9 with gelatinase activity, have been broadly associated with BBB breakdown and ICH [11,21].…”
Section: Discussionmentioning
confidence: 99%
“…Congenital FXIII deficiency is a rare bleeding disorder (RBD) with an autosomal recessive pattern of inheritance and estimated incidence of 1 per 2 million in the general population. The disorder is more common in Iran, especially Khash city (Khash factor XIII) with an incidence of 1 homozygote per ∼500 individuals and 3.5% heterozygotes, in this area [3][4][5][6][7]. Based on residual plasma FXIII level in patients with FXIII deficiency, bleeding symptoms can range from mild to severe such as intracranial hemorrhage (ICH).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation